To Study the Intervention of Bell’s Palsy by Video Self Modelling through Kinect Azure : A Research Protocol - Madhura R. Darware1 , Divya Jethwani2 (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Bell’s palsy is the common acute mono-neuropathy, and is commonly associated with facialparalysis or weakness of facial nerve. It is unilateral facial nerve paresis or paralysis. The cause of Bell’spalsy is suspected to be herpes simplex virus infection of nerve.The nerve get swollen because of thisviral infection and is compressed in its canal as it passes through the temporal bone. Grading systems forthe assessment of movements and asymmetry of face in Facial palsy are divided into computer-based andtraditional grading systems. The program that uses Kinect Azure provides assessment method for evaluationof asymmetry of face at rest and the rating of facial palsy during voluntary activity of various areas overface. This study aims to investigate the intervention of facial palsy by video self modelling with the use ofKinect Azure.Methods: 20 participants will be selected. Each group will include 10 subjects. Group A will receiveconventional treatment, electrical muscle stimulator(EMS) ,and visual feedback.Group B(Experimental group) will receive conventional treatment ,electrical muscle stimulator and videoself modelling. Each participant would be presented with their own videotape of video self-modeling, whichincluded the best attempts at their evenest acts (smiles).Following 2 weeks of tape viewing the actions willbe assessed. The outcome of the treatment will be assessed by Kinect Azure.Discussion: Traditional methods for documentation of treatment effect have been through scales andquestionnaires which at times are little complex and also difficult for patients to interpret. Hence thisexperimental and comparative study aims at focusing on the effective use of Kinect to document outcomefor bell’s palsy